Knowledge, Attitudes, Behavioural Practises, and Psychological Impact Relating to COVID-19 Among People Living With Spinal Cord Injury During In-Patient Rehabilitation in Bangladesh - Hossain, Mohammad Anwar; Hossain, K. M. Amran; Sakel, Mohamed; Kabir, Md. Feroz; Saunders, Karen; Faruqui, Rafey; Hossain, Mohammad Sohrab; Uddin, Zakir; Kader, Manzur; Walton, Lori Maria; Haque, Md. Obaidul; Shafin, Rubayet; et al. (Frontiers in Neurology, 2022)
Aim The aim of this research is to focus on gaining an insight into the knowledge, attitudes, behavioural practises (KAP), and psychological impact relating to COVID-19 among the people living with spinal cord injury receiving in-patient rehabilitation. Methods A prospective, cross-sectional survey of people with SCI (N = 207), who were in active in-patient rehabilitation from two tertiary SCI Rehabilitation Centres in Bangladesh. Data were collected via face-to-face interviews, after voluntary consent, using a pretested, language validated questionnaire on Knowledge, Attitude and Behavioural practises (KAP) and the Depression, Anxiety, Stress Scale (DASS-21). Ethical approval and trial registration were obtained prospectively. Results A total of 207 people with SCI responded, among which 87% were men and 13% were women, with a mean age of 34.18 ± 12.9 years. Within the sample group, people living with tetraplegia comprised 33.8%, and people living with paraplegia comprised 66.2%. Overall, 63.8% of the participants were diagnosed with an SCI categorised as ASIA-A. Overall, the “knowledge score” was 8.59 ± 2.3 out of 12, “depression” was 11.18 ± 8, “anxiety” was 7.72 ± 5.1, and “stress” was 9.32 ± 6.7 from a total of 21 scores each category. The strong correlation was between knowledge, DASS scores, and age (p < 0.05). In addition, there was a strong correlation between knowledge, gender (p < 0.05) and education (p < 0.01). Binary logistic regression found a stronger association of knowledge and DASS scores with gender, young age, illiteracy (p < 0.01), and rural residence (p < 0.05). A positive relationship was found between depression and anxiety scores (p < 0.01) and a moderate positive relationship was found between depression and stress scores (p < 0.01). A positive attitude was reported by the majority of participants (p < 0.05). In terms of behavioural practises, participants reported both self and caregiver had followed health advice with regard to consulting health professionals (65.7%), implementing isolation (63.8%), taking droplet precaution care (87.4%), and hygiene care (90.3%). Conclusion Participants in this study reported high levels of knowledge, adoption of positive attitudes, and the practise of positive health advisory behaviours related to COVID-19 prevention procedures. However, high levels of depression, anxiety, and stress were also reported. Overall, women and younger participants were more likely to have high KAP, whereas those living in rural areas and with literacy challenges were less likely to report high knowledge scores.